Zofia Filipowiczówna (1876–1900) – siostra „Joaś” i „Siłaczek” - Samborska-Kukuć, Dorota (Poznańskie Studia Polonistyczne. Seria Literacka, 2024)
Until now, no texts were written about Zofia Filipowiczówna (1876–1900), the author of a collection of poems and memoirs published posthumously as Pamiętnik (Diary) in 1905; she was not even identified as the sister of Tytus Filipowisz, a Polish Socialist Party activist. Similarly to her brother, Filipowiczówna was a socialist activist and an active member of youth organisations. Her activities, worldview, temperament, system of values and the course of her short life are reflected in letters to her cousins, Maria and Anna Surzyckie, archived by the Polish Academy of Sciences. This correspondence is complemented by Pamiętnik, an intimate and poetic record of Filipowiczówna’s reflections, struggles with her difficult fate and her attempts at overcoming weaknesses through altruistic Act, which were based on “the power of will”.